Developing the Extraordinary Potential: Inclusive Education as the Key to Developing the Talent of Children with Special Needs - Maknun, Lu'lu'il; Annaafi’atsaani, Irbasabila; Ikhrom, Ikhrom (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The purpose of this research is to understand the importance of inclusive education for developing the talents of children with special needs. Inclusive education plays a crucial role in optimizing the development of the talents of children with special needs. By providing equal and supportive access to education for children with various special needs, inclusive education creates a learning environment that allows them to develop their potential without limitations. Methods – The method used is library research, which involves collecting data by searching for sources and reconstructing it from various sources such as books, journals, and existing research. The data is then analyzed and filtered to obtain the research focus. Findings – Previous research findings, namely inclusive-based education, are the answer to education for all systems, namely a system that provides education and knowledge to all students without considering the differences between them. Through inclusive education, most students with special needs can reveal and develop their talents. The research results show that inclusive education helps children with special needs in Indonesia, helping them build life skills, independence, and decision-making. Inclusive education provides equal rights and opportunities for all students, enabling them to access education in regular schools. Parents, teachers, and the community have an important role in creating an environment that supports diversity and respects differences. Research Implications – This research is limited to library research; the results are a compilation of previous research findings and data from various sources, such as the internet, books, and journals. Therefore, it is recommended to apply the results of this research to subsequent field studies.